Survey of unlicensed and off label drug use in paediatric wards in European countries. Issue 7227 (8th January 2000) - Conroy, Sharon; Choonara, Imti; Impicciatore, Piero; Mohn, Angelika; Arnell, Henrik; Rane, Anders; Knoeppel, Carmen; Seyberth, Hannsjoerg; Pandolfini, Chiara; Raffaelli, Maria Pia; Rocchi, Francesca; Bonati, Maurizio; et al.
Abstract: Objective: To determine the extent of use of unlicensed and off label drugs in children in hospital in five European countries. Design: Prospective study of drugs administered to children in general paediatric medical wards over four weeks. Setting: Children's wards in five hospitals (one each in the United Kingdom, Sweden, Germany, Italy, and the Netherlands). Subjects: Children aged 4 days to 16 years admitted to general paediatric medical wards. Main outcome measure: Proportion of drugs that were used in an unlicensed or off label manner. Results: 2262 drug prescriptions were administered to 624 children in the five hospitals. Almost half of all drug prescriptions (1036; 46%) were either unlicensed or off label. Of these 1036, 872 were off label and 164 were unlicensed. Over half of the patients (421; 67%) received an unlicensed or off label drug prescription. Conclusions: Use of off label or unlicensed drugs to treat children is widespread. This problem is likely to affect children throughout Europe and requires European action.